(untitled) (Medico Legal Update, 2019)
People who have health insurance feel comfortable and safe because their health is protected. If they are hospitalized, there is an institution that pays, so that efforts to prevent themselves from becoming sick are forgotten. People are reluctant to take preventive measures, such as being lazy to eradicate mosquito nests. The purpose of this study was to analyze the relationship between knowledge, attitudes towards health insurance, eradication of mosquito breeding places, and the incidence of dengue hemorrhagic fever in Badung Regency. This type of research was observational, involving 330 people as sample selected by cluster sampling. The cluster number was 10, each cluster consisted of 33 respondents. The cluster was selected using the Probability Proportional to Size (PPS) technique. Data were collected through filling out questionnaires and then analyzed using multivariate statistics. The results showed that there was a positive correlation between knowledge and attitude and the incidence of dengue hemorrhagic fever; negative correlation between knowledge and attitude with the act of eradicating mosquito nests; and a negative correlation between action and the incidence of dengue hemorrhagic fever. It is hoped that the community will be more active in doing voluntary work or cleaning the environment periodically, both weekly and monthly.